"EXPLORE CUSTOMER SATISFACTION LEVEL IN DIGITAL E-BANKING:A QUALITATIVE STUDY ON SELECTIVE COOPERATIVE BANKS IN GUJARAT" (CAHIERS MAGELLANES-NS, 2024)
The global financial improvement and reach needs digital E-banking and its related services. The cooperative sector has more reach in rural India as well as also strong foundation in Gujarat. The present paper mostly focuses on the overall satisfaction level of banking customers in digital E-banking services provided by cooperative banks. The study depends on the primary research as well as the random sampling method used for the collection of the 290 samples. The study has found no significant variation among cooperative banks for providing digital E-banking services.  Moreover, significant variation was found among different categories of satisfaction levels in different selected variables. Further, a positive satisfaction level is lower than a Negative satisfaction level which indicates a significant difference between a positive satisfaction level and a Negative satisfaction level where a Negative satisfaction level is higher than positive satisfaction. It indicates cooperative banks need to improve digital E-banking services.